A Case Report of Gastric Diverticulum-An Uncommon Cause of Dyspepsia - Muhamad Amzar; Ikhwan Sani Mohamad; Syed Hassan Syed Aziz; Wan Mokhzani Wan Mokhter; Siti Rahmah Hashim Isa Merican (Acta Medica Iranica)
Gastric diverticulum is a rare anatomic abnormality which resulted from abnormal outpouching of the stomach wall. It is known to cause symptoms from asymptomatic to life threatening conditions. The management mainly depends on the severity of the disease and the size of the diverticulum and there is no specific treatment for an asymptomatic patient. We reported a case of 58-year-old gentleman who presented with dyspepsia secondary to gastric diverticulum. The diagnosis was made based on medical history and an outpatient Oesophagogastroduodenoscopy (OGDS). Patient was treated non surgically with proton pump inhibitors and prokinetics.